Efficacy of Oral Cochleate-Amphotericin B in a Mouse Model of Systemic Candidiasis - Santangelo, Rosaria (American Society for Microbiology, 2000)
Amphotericin B (AMB) remains the principal therapeutic choice for deep mycoses. However, its application is limited by toxicity and a route of administration requiring slow intravenous injection. An oral formulation of this drug is desirable to treat acute infections and provide prophylactic therapy for high-risk patients. Cochleates are a novel lipid-based delivery system that have the potential for oral administration of hydrophobic drugs. They are stable phospholipid-cation crystalline structures consisting of a spiral lipid bilayer sheet with no internal aqueous space. Cochleates containing AMB (CAMB) inhibit the growth of Candida albicans, and the in vivo therapeutic efficacy of CAMB administered orally was evaluated in a mouse model of systemic candidiasis. The results indicate that 100% of the mice treated at all CAMB doses, including a low dosage of 0.5 mg/kg of body weight/day, survived the experimental period (16 days). In contrast, 100% mortality was observed with untreated mice by day 12. The fungal tissue burden in kidneys and lungs was assessed in parallel, and a dose-dependent reduction in C. albicans from the kidneys was observed, with a maximum 3.5-log reduction in total cell counts at 2.5 mg/kg/day. However, complete clearance of the organism from the lungs, resulting in more than a 4-log reduction, was observed at the same dose. These results were comparable to a deoxycholate AMB formulation administered intraperitoneally at 2 mg/kg/day (P < 0.05). Overall, these data demonstrate that cochleates are an effective oral delivery system for AMB in a model of systemic candidiasis.